Thermal Conductivity Enhancement of Iraqi Origin Paraffin Wax by Nano-Alumina - Chaichan, Miqdam T.; Hussein, Rasha Mohammed; Jawad, Aida Mohammed (Al-Khwarizmi Engineering Journal, 2017)
Abstract Paraffin wax is utilized for the heat storage applications taking advantage from the high stored latent heat during the phase change (from solid to fluid) period. What isn't right with this procedure is that the wax has a little heat transfer rate because of its low thermal conductivity. The thermal conductivity improvement of the paraffin wax has been examined utilizing nano-material with high thermal conductivity. In the recent study, (Al2O3) nanoparticles with weights of 1, 2, and 3% of the paraffin wax were added to the paraffin wax. The Iraqi paraffin wax accessible at the local markets was utilized as a phase change material (PCM).Many properties of the wax were changed due to the addition of nanofillers. The wax color was changed from light brown to white. The thermal conductivity of the paraffin wax was expanded by increasing the additional nanoparticles extent with 37.1, 42.3 and 60.32% for 1, 2 and 3% added nano-Al2O3 compared to pure wax conditions. The subsequent change in the thermal conductivity of the paraffin wax makes it reasonable for the use in thermal storage applications. Keywords: Latent heat, Nano-alumina, Paraffin wax, Thermal storage,